Engeletin Targets Mitochondrial Dysfunction to Attenuate Oxidative Stress and Experimental Colitis in Intestinal Epithelial Cells Through AMPK/SIRT1/PGC-1α Signaling - Jing Li; Zhijun Geng; Lixia Yin; Ju Huang; Minzhu Niu; Keni Zhang; Xue Song; Yueyue Wang; Lugen Zuo; Jianguo Hu (Antioxidants)
Inflammatory bowel disease (IBD), encompassing Crohn’s disease and ulcerative colitis, is characterized by chronic intestinal inflammation and epithelial barrier disruption. Emerging evidence highlights mitochondrial dysfunction as a pivotal contributor to IBD pathogenesis, where impaired mitochondrial homeostasis in intestinal epithelial cells (IECs) disrupts redox balance, exacerbates oxidative stress, and triggers apoptosis, further compromising barrier integrity. This study investigated the therapeutic effects of Engeletin (Eng), a dihydroflavonoid from Smilax glabra Roxb., in dextran sulfate sodium (DSS)-induced colitis mice and colonic organoid models. Eng administration (10, 20, 40 mg/kg) significantly alleviated colitis symptoms, including weight loss, disease activity index (DAI) scores, and colon shortening, while restoring intestinal barrier integrity through the upregulation of tight junction proteins (ZO-1, claudin-1) and goblet cell preservation. Eng suppressed NF-κB-mediated inflammation and activated the Nrf2 antioxidant pathway, as well as reduced oxidative stress markers (MDA, CAT, GSH, and SOD). It attenuated epithelial apoptosis by balancing pro- and anti-apoptotic proteins (Bax/Bcl2, c-caspase3) and ameliorated mitochondrial dysfunction via enhanced ATP production, mtDNA levels, and complex I/IV activity. Mechanistically, Eng activated the AMPK/SIRT1/PGC-1α axis, and pharmacological inhibition of PGC-1α abolished its mitochondrial protective and anti-apoptotic effects. These findings demonstrate that Eng alleviates colitis by targeting mitochondrial homeostasis and oxidative stress through AMPK/SIRT1/PGC-1α signaling, offering a multitargeted strategy for IBD therapy.